Distance Education in the COVID crisis - 19: an experience report (Research, Society and Development, 2020)
This text deals with the subject of Distance Education (DE) in the midst of the COVID-19 crisis. To this end, it aims to understand the concepts and foundations of distance education, in order to analyze the perceptions of students, as to distance education as a strategy to resolve the losses in the teaching and learning process at EPT, due to the Covid Pandemic. It is methodologically guided by the bibliographic technique and the presentation of data that draw the perceptions of students enrolled in face-to-face courses about distance education classes. The data were analyzed and discussed, from categories. Thus, this article is divided into three sections, namely: a) it addresses the concepts and foundations of distance education; b) deals with the challenges and possibilities of distance education in Federal Education Institutes, in the face of the pandemic; c) presents the students' perception of remote activities, especially the Philosophy course. It is concluded that the Covid-19 Pandemic was, in some way, a privileged moment of recognition of the weaknesses and potentialities as an educational community.